Traceability and control as levers to prevent leakage from legal circulation when legalizing medical cannabis - Gruzieva, Tetiana S.; Korchevnyy, Andrii I.; Palii, Maksym V.; Diachenko, Karina O.; Korolenko, Volodymyr V.; Короленко, Володимир Васильович (Polish Medical Association, 2024)
Aim: To reveal traceability and control as levers to prevent leakage from legal circulation when legalizing medical cannabis. PATIENTS AND METHODS: Materials and Methods: The methodological basis of this research work is based on a systematic approach. Methods of structural and logical analysis, bibliosemantic, abstraction and generalization were used in this article. RESULTS: Results: The analysis of the regulatory framework and regulatory initiatives in the field of circulation of narcotic drugs, in particular, cannabis (in total 56 documents) demonstrated repeated attempts to reform it in Ukraine in order to increase the availability and efficiency of medical and pharmaceutical services. Recently adopted law on the legalization of medical cannabis pays special attention to the traceability of the circulation of medical cannabis and cannabis-based medicines (CbMs) by digitalization and creation of the appropriate electronic information system. CONCLUSION: Conclusions: With the adoption of the law on the legalization of medical cannabis Ukraine became the 57th country in the world to legalize such cannabis. The study and analysis of the regulatory framework of Ukraine, taking into account the best world practices, showed that the legalization of medical cannabis will allow for providing more effective care to many patients including wounded defenders.
Keywords: cannabis; narcotic drugs; control; drug policy; medical cannabis; traceability